Profitability, Audit Oversight, and Their Impact on Firm Value: Evidence from Indonesia’s Mining Sector - Yudhi Prasetiyo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Understanding the determinants of firm value is a critical issue in corporate finance, particularly in emerging markets where governance, transparency, and efficiency differ from developed economies. This study examines the effect of Gross Profit Margin (GPM), Return on Investment (ROI), and audit committee size on firm value, proxied by Tobin’s Q, using 70 observations from mining companies listed on the Indonesian Stock Exchange during 2021–2022. Panel data regression with specification tests (Chow, Hausman, and Breusch-Pagan) identifies the Random Effects Model (REM) as the most appropriate estimation method. The findings reveal that GPM has a significant negative effect on Tobin’s Q. This paradox indicates that higher profitability, when not supported by strategic positioning and operational sustainability, may be undervalued by the market, especially under conditions of limited transparency and weak investor trust. In contrast, ROI and audit committee size show no significant impact, suggesting that financial returns and numerical governance structures alone are insufficient indicators of firm value. These results highlight the complexity of value creation in emerging markets, emphasizing the importance of combining profitability with strong governance, transparency, and strategic execution. The study provides insights for managers, investors, and policymakers in strengthening governance practices and fostering sustainable firm value growth.